2022
DOI: 10.1002/anie.202207184
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Solid‐Electrolyte Interphase Formation on Silicon Electrodes Revealed by Combinatorial Electrochemical Screening

Abstract: Revealing how formation protocols influence the properties of the solid-electrolyte interphase (SEI) on Si electrodes is key to developing the next generation of Li-ion batteries. SEI understanding is, however, limited by the low-throughput nature of conventional characterisation techniques. Herein, correlative scanning electrochemical cell microscopy (SECCM) and shellisolated nanoparticles for enhanced Raman spectroscopy (SHINERS) are used for combinatorial screening of the SEI formation under a broad experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 48 publications
0
51
0
3
Order By: Relevance
“…Environmental control during the experiment has been another major point of interest. ,, Oil has been used to cover the substrate and restrict gas exchange from the meniscus,; while small containers connected to a gas supply were utilized to establish specific atmospheric conditions. Recently, SECCM measurements have been conducted inside a glovebox, ,, and aided by a thorough understanding of the behavior of nonaqueous electrolyte media, they have set the groundwork for future work into battery materials.…”
Section: High-throughput Scanning Electrochemical Cell Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental control during the experiment has been another major point of interest. ,, Oil has been used to cover the substrate and restrict gas exchange from the meniscus,; while small containers connected to a gas supply were utilized to establish specific atmospheric conditions. Recently, SECCM measurements have been conducted inside a glovebox, ,, and aided by a thorough understanding of the behavior of nonaqueous electrolyte media, they have set the groundwork for future work into battery materials.…”
Section: High-throughput Scanning Electrochemical Cell Microscopymentioning
confidence: 99%
“…Slow scan rate SECCM voltammetry revealed that step edges promote electrolyte reduction resulting in a more passivating SEI layer than on the basal plane . In recent work, SECCM measurements were coupled with enhanced Raman spectroscopy monitoring via shell-isolated nanoparticles (SHINERS technique, Figure D) . Two different aprotic electrolyte systems (ethylene carbonate/ethyl methyl carbonate, vol.…”
Section: High-throughput Scanning Electrochemical Cell Microscopymentioning
confidence: 99%
“…209,226,[235][236][237][238][239] Oil has been used to cover the substrate and restrict gas exchange from the meniscus; 226 while small containers connected to a gas supply were utilized to establish specific atmospheric conditions. Recently, SECCM measurements have been conducted inside a glovebox, 236,239,240 and aided by a thorough understanding of the behavior of non-aqueous electrolyte media, 241 they have set the groundwork for future work into battery materials.…”
Section: Technical and Theoretical Developmentsmentioning
confidence: 99%
“…236 In recent work, SECCM measurements were coupled with enhanced Raman spectroscopy monitoring via shell-isolated nanoparticles (SHINERS technique, Figure 11D). 240 Two different aprotic electrolyte systems (ethylene carbonate/ethyl methyl carbonate, vol. 1:1; and propylene carbonate) were used to perform local cyclic voltammetry on (111)-facet silicon.…”
Section: Battery Electrode Materialsmentioning
confidence: 99%
“…The most crucial electrochemical energy storage technology for electric vehicles, portable electronics, and other high-energy-demanding devices is lithium (Li)-ion batteries. However, their current graphite electrodes have poor specific energy and delayed Li + insertion kinetics, and, therefore, extensive research is being done to find novel electrode materials that will address these issues. Silicon, tin, phosphorus, , or transition-metal oxides promised high Li-storage capacity and energy, but their performance degraded greatly due to volume change during lithiation and delithiation, which led to dead active materials and a poor solid–electrolyte interface (SEI). Synthetic carbon materials, designable from organic starting materials, unlike their crystalline counterparts, welcome large-extent heterodoping and pore management, which is of great benefit for obtaining large Li-storage capacity at high rates. , …”
Section: Introductionmentioning
confidence: 99%